Comparative characteristics of chosen aspects of tobacco smoking among the students of Poznan University of Medical Sciences and students of vocational medical colleges in Poznań - Korzeniowska, Katarzyna Agnieszka; Pawlaczyk, Magdalena; Cieślewicz, Artur; Jabłecka, Anna (Journal of Medical Science, 2018)
Aim. Medical doctors, nurses, pharmacists, and paramedics are professions placing themselves highest in the rankings of occupations granted public trust. The knowledge of the negative impact of tobacco use on physical condition possessed by those occupational groups ought to limit the addiction among this population, which should constitute a benchmark of health‑promoting attitude for the public. Many health‑promoting decisions are made during the period of studies. The study aimed to establish the scale of tobacco smoking and the profile of chosen aspects of this issue among students of Poznan University of Medical Sciences and students of vocational medical colleges in Poznań. Material and Methods. An author questionnaire was conducted. 586 students (471 University students, 115 college students) aged between 19 and 65 completed the survey.Results. The majority (76.62%) of the surveyed students were non‑smokers. Smokers were predominately male (the entire surveyed population, University students). Medical college students smoked more cigarettes daily compared to the University students. The most commonly declared reason for smoking was the social purpose. Among former smokers, female more often than male indicated health considerations and the knowledge of harmful effects of smoking as reasons for quitting; among college students, the most common reason was health considerations, whereas University students listed knowledge of the harmfulness of smoking, health considerations, and other motives most often.Conclusions. Both University students and medical college students smoked more rarely than their contemporaries in the general population. The respondents constitute a group displaying relatively high prevalence of health‑promoting attitudes.